When the two ends meet: An experiment on cooperation across the Italian North-South divide - Pietro Battiston; Simona Gamba (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
We study the behavior of individuals coming from different geographic regions of Italy, in a same public good game. We confirm previous findings according to which, faced with the same incentives and experimental conditions, Southern citizens exhibit a lower propensity to cooperate than Northern ones. This difference is mainly explained by a gap in the impact of coordination devices available to participants, as we show by manipulating them. Most importantly, when subjects with different geographic origins are teamed up together, their contributions decrease with respect to homogeneous groups, again because of a reduced effect of coordination devices. These findings reinforce the interpretation of the Italian South-North divide as related to trust, prejudice and a consequent path-dependence in levels of social capital, rather than due to the mere effect of differences in institutions and economic opportunities.
Keywords: A13; C71; C92; H41; 330; public good; cooperation; social capital; cultural differences; laboratory experiment